Wojciech Dajczak, The Nature of the Contract in Reasoning of Civilian Jurists, 2012 - Wojciechowski, Rafał (Czasopismo Prawno-Historyczne, 2013)
Wojciech Dajczak, The Nature of the Contract in Reasoning of Civilian Jurists, 2012